CAVITATION EROSION MICRO-JETS STUDIES OF ALUMINUM SPECIMENS WITH THE AID OF THE COMPACT ROTATING DISK DEVICE - Bazanini, G.; Unfer, R. K.; Lima, N. N. C. (Revista de Engenharia Térmica, 2020)
The shape of micro-jets created in the final stages of cavities collapses are studied here with the goal to explain the shape of the pits, formed on the surface of commercial aluminum specimens. These marks on the specimen surfaces are obtained experimentally with the aid of the compact rotating disk device and a scanning electronic microscope. Some explain is attempt, based on the theories of the potential flow and forms.